Basic life support training targeted to family members or carers of those at high-risk of out-of-hospital cardiac arrest: a systematic review - Zakary Doherty; Janet E. Bray; Judith Finn; Susie Cartledge (Resuscitation Plus, 2025)
Introduction: This updated systematic review examined the impact of targeting basic life support (BLS) training to groups at high risk of out-of-hospital cardiac arrest (OHCA) on patient and educational outcomes. Methods: Searches of databases (MEDLINE, EMBASE, CINAHL and Cochrane Library) were conducted from June 2014 to November 2024 (PROSPERO CRD42021233811). We identified pre-2014 studies from the 2015 International Liaison Committee on Resuscitation evaluation of this topic. Two reviewers independently screened titles and full-text papers, extracted data and assessed risk of bias (ROB-2 and ROBINS-I). The certainty of the evidence for each outcome was evaluated using GRADE methodology. A narrative synthesis was performed. Results: A total of 48 studies (17 new non-randomised studies) were found. While there is evidence of subsequent use of skills and improved survival with the intervention, the quality of evidence remains very-low to low, due to the low number of OHCA events during follow-up and significant loss to follow-up. For educational outcomes, the quality of evidence for CPR skills, confidence and willingness to perform CPR was low to moderate, with most studies showing improvements in these outcomes or skills at guideline recommendations following training. Those trained were also likely to train others. Conclusions: Despite a large number of studies examining BLS training to those at high-risk of OHCA, the quality of evidence remained largely unchanged. However, the evidence continues to demonstrate that targeting those at high-risk improves simulated CPR skills, and confidence and willingness to provide CPR in likely rescuers.